Temperature effects on electrical performance of carbon‐based nano‐interconnects at chip and package level. (14th February 2013) - Chiariello, Andrea G.; Maffucci, Antonio; Miano, Giovanni
SUMMARY: This paper investigates the electrical performance of innovative carbon‐based nano‐interconnects made by carbon nanotubes and graphene nanoribbons. The electronic transport in the carbon materials is modeled in the frame of the Transmission Line theory, where the classical per‐unit‐length circuital parameters are corrected by new terms arising from the quantistic nature of the transport. These parameters are related to the number of the conducting channels and the mean free path, which in turn, are expressed as functions of temperature and size. By coupling this model to the heat equation, a simple electro‐thermal model is derived. Case‐studies are carried out with reference to 22‐nm technology node applications. Copyright © 2013 John Wiley & Sons, Ltd.